Pressure and guest-mediated pore shape modification in a small pore MOF to 1200 bar. Issue 82 (22nd September 2022) - McMonagle, Charles J.; Turner, Gemma F.; Jones, Isabelle; Allan, David R.; Warren, Mark R.; Kamenev, Konstantin V.; Parsons, Simon; Wright, Paul A.; Moggach, Stephen A.
Abstract : Guest-mediated flexibility in the metal–organic framework, Sc2 BDC3, is examined under moderate pressure in a sapphire capillary cell, revealing pore-shapes changes at much lower pressures than previously reported. Abstract : Guest-mediated pore-shape modification of the metal–organic framework, Sc2 BDC3 upon adsorption of n -pentane and isopentane is examined from 50–1200 bar. Rotation of the BDC linker responsible for the change in pore shape occurs at much lower pressures than previously reported, with distinct adsorption behaviour observed between pentane isomers.